Novel Mutations in the Asparagine Synthetase Gene (ASNS) Associated With Microcephaly - Schleinitz, Dorit; Seidel, Anna; Stassart, Ruth; Klammt, Jürgen; Hirrlinger, Petra G.; Winkler, Ulrike; Köhler, Susanne; Heiker, John T.; Schönauer, Ria; Bialek, Joanna; Krohn, Knut; Hoffmann, Katrin; et al. (Frontiers in Genetics, 2018)
Microcephaly is a devastating condition defined by a small head and small brain compared to the age- and sex-matched population. Mutations in a number of different genes causative for microcephaly have been identified, e.g. MCPH1, WDR62, and ASPM. Recently, mutations in the gene encoding the enzyme asparagine synthetase (ASNS) were associated to microcephaly and so far 24 different mutations in ASNS causing microcephaly have been described. In a family with two affected girls, we identified novel compound heterozygous variants in ASNS (c.1165G>C, p.E389Q and c.601delA, p.M201Wfs*28). The first mutation (E389Q) is a missense mutation resulting in the replacement of a glutamate residue evolutionary conserved from Escherichia coli to Homo sapiens by glutamine. Protein modeling based on the known crystal structure of ASNS of E. coli predicted a destabilization of the protein by E389Q. The second mutation (p.M201Wfs*28) results in a premature stop codon after amino acid 227, thereby truncating more than half of the protein. The novel variants expand the growing list of microcephaly causing mutations in ASNS.